Approximate Diagonalization - Davies, E. B. (SIAM journal on matrix analysis and applications, 2007)
We describe a new method of computing functions of highly nonnormal matrices by using the concept of approximate diagonalization. We formulate a conjecture about its efficiency and provide both theoretical and numerical evidence in support of the conjecture. We apply the method to compute arbitrary real powers of highly nonnormal matrices.